2015
DOI: 10.4317/medoral.20341
|View full text |Cite
|
Sign up to set email alerts
|

Increased nuclear β-catenin expression in oral potentially malignant lesions: A marker of epithelial dysplasia

Abstract: BackgroundDeregulation of ?-catenin is associated with malignant transformation; however, its relationship with potentially malignant and malignant oral processes is not fully understood. The aim of this study was to determine and compare the nuclear ?-catenin expression in oral dysplasia and oral squamous cell carcinoma (OSCC). Material and MethodsCross sectional study. Immunodetection of ?-catenin was performed on 72 samples, with the following distribution: 21 mild dysplasia, 12 moderate dysplasia, severe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…By focusing in oral lesions, we and others have observed that β-catenin is progressively accumulated in the nucleus of dysplastic cells, as shown in cultured DOK and patient biopsies. 9,10 In fact, our more recent studies demonstrate that nuclear accumulation of β-catenin gradually augments from mild through moderate and severe dysplasia, and that these changes are associated with augmented Wnt3a in tissue biopsies. 12 Aside the requirement of Wnt ligands for nuclear accumulation of β-catenin in malignancy, 39,40 no information is available regarding molecular mechanisms involved in aberrant stabilization of β-catenin in premalignant lesions.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…By focusing in oral lesions, we and others have observed that β-catenin is progressively accumulated in the nucleus of dysplastic cells, as shown in cultured DOK and patient biopsies. 9,10 In fact, our more recent studies demonstrate that nuclear accumulation of β-catenin gradually augments from mild through moderate and severe dysplasia, and that these changes are associated with augmented Wnt3a in tissue biopsies. 12 Aside the requirement of Wnt ligands for nuclear accumulation of β-catenin in malignancy, 39,40 no information is available regarding molecular mechanisms involved in aberrant stabilization of β-catenin in premalignant lesions.…”
Section: Discussionmentioning
confidence: 90%
“…The latter is important, based on the ability of Rab5 to control early endosome dynamics, which may impinge in the acquisition of malignant traits in tumor cells, and most importantly, in oral dysplasia. In this context, the accumulation of nuclear β‐catenin in tumor cells and in oral dysplasia is striking, since these phenomena could be due to increased endosomal targeting of the β‐catenin destruction complex. Here, we explored whether endosomal sequestration of the destruction complex accounts for increased accumulation of nuclear β‐catenin in oral dysplasia and assessed the role of the endocytic protein, Rab5, in these events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After activation of canonical WNT signaling, cytoplasmic β-catenin dissociates from the cadherin-catenin protein complex, translocates, and accumulates in the nucleus, where β-catenin interacts with TCF/LEF to induce downstream gene expression ( Figure 3). In this way, cell proliferation, migration, or invasion can be affected [60].…”
Section: Epithelial Cadherinmentioning
confidence: 99%
“…After reading the titles and abstracts, 54 studies were considered potentially eligible and their full text was read by three reviewers. Seventeen articles met all inclusion criteria and were selected for this systematic review (5,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The selected articles were observational studies published between 2007 and 2018, all of them in English.…”
Section: Resultsmentioning
confidence: 99%